Prognostic value of epithelial–mesenchymal transition circulating tumor cells in female breast cancer: A meta-analysis - Zhao, Qiang; Li, Bingbing; Gao, Qi; Luo, Yang; Ming, Liang (Frontiers in Oncology, 2022)
Background: Epithelial-mesenchymal transition (EMT) conferred metastatic properties on circulating tumor cells (CTCs) and was considered to be correlated with bad survival outcomes in patients with breast cancer. However, different studies have reported controversial results regarding the relationship between CTCs that have undergone EMT (EMT-CTCs) and prognosis of breast cancer. Therefore, this meta-analysis aimed to investigate the prognostic role of EMT-CTCs in patients with breast cancer. Methods: In total, 842 patients from nine studies that were screened from the Web of Science, Embase, and PubMed were included. The hazard ratio (HR) and 95% confidence interval (CI) for progression-free survival (PFS) and overall survival (OS) were extracted or estimated by the Kaplan-Meier survival curve for the meta-analysis. Sensitivity analysis was performed to characterize heterogeneity among the trials. Meanwhile, subgroup analysis was performed to present the effects of cancer stage, identification method, sampling volume and region on the prognostic value of EMT-CTCs. Results: The pooled HRs for PFS were 1.97 (univariate: 95% CI, 1.19 - 3.24; P = 0.008) and 2.23 (multivariate: 95% CI, 1.29 - 3.86; P = 0.004). The pooled HRs for OS were 2.03 (univariate: 95% CI, 1.07 - 3.84; P = 0.029) and 1.70 (multivariate: 95% CI, 1.14 - 2.52; P = 0.009). Subgroup analysis showed that EMT-CTCs was associated with PFS in the primary breast cancer group (pooled HR = 2.58, 95% CI, 1.66 - 4.00, P < 0.001); the polymerase chain reaction (PCR) group (pooled HR = 2.69, 95% CI, 1.66 - 4.35, P < 0.001); the sampling volume of > 7.5 mL group (pooled HR = 1.93, 95% CI, 1.36 - 2.73, P < 0.001); and the Asia group (pooled HR = 1.92, 95% CI, 1.13 - 3.29, P = 0.017) and OS in the primary breast cancer group (pooled HR = 3.59, 95% CI, 1.62 - 7.95; P = 0.002). Conclusion: The meta-analysis showed that EMT-CTCs were associated with poorer survival outcomes in patients with breast cancer. More accurate methods and designed clinical trials with unified standards are essential to establish the real role of EMT-CTCs in disease progression in women with breast cancer.